Impact of farmer-managed maintenance of secondary canals on water distribution equity: a case study from Sindh, Pakistan - Lashari, Bakhshal, author; Murray-Rust, D. Hammond, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
International Irrigation Management Institute (IIMI) carried over a pilot action research study on farmer managed irrigation system (FMIS) in Sindh Province of Pakistan. Overall fourteen Farmer Organizations (FOs) on distributary channels were formed. In order to ensure success of this participatory management, the FO members were trained in organizational management, operation and maintenance (O&M) of channels and financial aspects. The study focuses on impact of farmer managed maintenance on water distribution equity and resources mobilization. In conjunction with a program to organize water users at secondary canals in Sindh, IIMI staff made observations on the physical conditions before and after the maintenance campaign in January 2000 and actual inputs made by members of Farmer Organizations. In a one-week period water users contributed over 7,800 man-days of labor and 582 hours of tractor operation in eight secondary canals, and removed over 43,000 cubic meters of sediment. The imputed cost of these contributions exceeded over Rs.900,000 ($15,000) or almost Rs.30 per hectare ($0.50). The hydraulic benefits were substantial. Comparing water deliveries into the head and tail reach of each canal before desilting, head end areas received roughly 68% more water than tail enders. After desilting the head end areas only received 14% more water, and in six of the eleven canals where water measurements were taken, tail end areas actually received more water than head end areas. Despite the benefits that accrued, there is concern for the long-term sustainability of the improved performance. There is no systematic monitoring program that enables operation and maintenance to be linked and no proper maintenance of control infrastructure to complement desilting. Until these institutional changes occur, operation and maintenance will remain a largely ad-hoc activity.
USCID/EWRI conference
Farmer-managed maintenance, Sindh, Pakistan
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.